2018
DOI: 10.1177/1082013217753898
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and nano-capsulated fungal pectinase with outstanding capabilities of eliminating turbidity in freshly produced juice

Abstract: The present study aimed to compare the pectinase forms produced from Trichoderma viride-free, micro-capsule, and nano-capsule-in sodium alginate to analyze the pectin that causes the turbidity of orange juice. This was performed along with an estimation of viscosity, residual of pectin, and turbidity. The extracted and purified enzyme was 24.35-fold better than that of the crude enzyme. After application of free one, it loses most of the activity on low degrees of acidity and remains constant on the temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The most prominent polymers are chitosan and sodium alginate, which may be related to the abundance of these polymers in nature. Furthermore, most authors reported high encapsulation efficiency [ 16 , 19 , 57 , 138 , 140 , 152 , 154 ], improvement or maintenance of enzyme activity [ 16 , 19 , 57 , 138 , 144 , 148 , 151 , 152 , 162 ], improved pH, temperature or storage stability [ 150 , 151 , 152 , 158 , 161 ], and high reuse capacity [ 132 , 163 ]. The most widely used methods for entrapping enzymes are described in the next sections.…”
Section: Enzyme Encapsulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent polymers are chitosan and sodium alginate, which may be related to the abundance of these polymers in nature. Furthermore, most authors reported high encapsulation efficiency [ 16 , 19 , 57 , 138 , 140 , 152 , 154 ], improvement or maintenance of enzyme activity [ 16 , 19 , 57 , 138 , 144 , 148 , 151 , 152 , 162 ], improved pH, temperature or storage stability [ 150 , 151 , 152 , 158 , 161 ], and high reuse capacity [ 132 , 163 ]. The most widely used methods for entrapping enzymes are described in the next sections.…”
Section: Enzyme Encapsulation Methodsmentioning
confidence: 99%
“…The enzyme leakage from capsules increased with an increase in the duration of the simulated cheese press from 4 to 16 h, but the control of the amount of enzyme leakage is still needed to direct the proteolysis required for optimal flavor development in accelerated cheese ripening. Microbial pectinase encapsulated by sodium alginate was used successfully by Mahmoud et al [ 163 ] to eliminate pectin from orange juice, reducing turbidity since the free enzyme cannot be used in this case due to the high acidity of the juice.…”
Section: Applications Of Polymer Encapsulated Enzymesmentioning
confidence: 99%
“…71 Mahmoud et al also used sodium alginate to encapsulate pectinase, which could be used to hydrolyze pectin in orange juice by natural means and greatly improve the use of pectinase after encapsulation. 72 3.3.3. Hyaluronic acid.…”
Section: Polysaccharide Polymersmentioning
confidence: 99%